2022
DOI: 10.1021/acscatal.2c01713
|View full text |Cite
|
Sign up to set email alerts
|

Selective Functionalization of Arene C(sp2)–H Bonds by Gold Catalysis: The Role of Carbene Substituents

Abstract: The complete regioselective incorporation of carbene units to nonactivated arene rings has been achieved employing gold(I) catalysts bearing alkoxydiaminophosphine ligands, with readily available, nonelaborated ethyl 2-phenyldiazoacetate as the carbene source. These results are in contrast with the scarce precedents which required highly elaborated diazo substrates. Density functional theory (DFT) calculations have revealed the important role of the R group in the C(R)CO 2 Et fragment, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Initially, we commenced with the reaction of ethyl α - phenyl-α - diazoacetate 1a′ and benzene 2a using well-established metal catalysts that have long been explored for the C–H bond functionalization of aromatic compounds with α-aryl-α-diazoacetates in dry benzene (Table , entries 1–7). Rhodium, copper, and gold catalysts were found to be ineffective for the C–H bond functionalization of benzene at room temperature as well as under refluxing conditions (Table , entries 1–7). We observed that in all the cases (rhodium, copper, and gold catalysis), reactions led to very fast decomposition of diazo acetate 1a′ to afford a complex inseparable reaction mixture (dark brown color).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, we commenced with the reaction of ethyl α - phenyl-α - diazoacetate 1a′ and benzene 2a using well-established metal catalysts that have long been explored for the C–H bond functionalization of aromatic compounds with α-aryl-α-diazoacetates in dry benzene (Table , entries 1–7). Rhodium, copper, and gold catalysts were found to be ineffective for the C–H bond functionalization of benzene at room temperature as well as under refluxing conditions (Table , entries 1–7). We observed that in all the cases (rhodium, copper, and gold catalysis), reactions led to very fast decomposition of diazo acetate 1a′ to afford a complex inseparable reaction mixture (dark brown color).…”
Section: Resultsmentioning
confidence: 99%
“…As the α-diazocarbonyl compounds can be easily prepared from readily available starting materials, the utility of α-diazocarbonyl compounds in aromatic C–H bond functionalization has grown over the years. ,, Efforts have been made to increase the practicality of these protocols for the aromatic C–H bond functionalization by modifying catalysts and/or α-diazocarbonyl reagents for the aromatic C–H bond functionalization. The transition metal complexes of rhodium, gold, copper, and iron have been widely used for the aromatic C–H bond functionalization reactions with α-diazocarbonyl compounds. Recently, Pérez and co-workers have utilized the manganese catalyst for the aromatic C–H bond functionalization using α-diazocarbonyl compounds .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40][41] Siteselective transformations often occur at the least sterically demanding para-position. [42][43][44][45][46][47] Meanwhile, state-of-the-art biocatalytic systems have been limited to electron-rich heteroaromatics. 48,49 Inspired by these precedents, we set out to engineer carbene transferases that favor arene C-H functionalization, in order to complement reported "C(sp 3 )-H alkylases".…”
Section: Introductionmentioning
confidence: 99%
“…However, the enantioselective version is challenging for the following two reasons. (a) The linear geometry of gold(I) complexes made it difficult to deliver chiral information from the chiral ligand; [10, 11] (b) On the basis of previous mechanistic studies, [9j–m] the key step for chiral induction is the formation of the final ester product from enols via a proton transfer assisted by water as a proton shuttle, in which the gold complex is leaving or far away from the chiral carbon center. Given the fact that the combination of gold catalyst and chiral organocatalyst has emerged as an alternative approach for asymmetric gold catalysis, [12, 13] and chiral phosphoric acid (CPA) is an excellent proton shuttle, [14] we hypothesize that the asymmetric para ‐C(sp 2 )−H bond functionalization of alkyl benzenes with diazoesters could be achieved via cooperative catalysis of gold and CPA.…”
Section: Introductionmentioning
confidence: 99%